Analysis of outcomes in adolescents and young adults with chronic myelogenous leukemia treated with upfront tyrosine kinase inhibitor therapy - Naveen Pemmaraju; Hagop Kantarjian; Jianqin Shan; Elias Jabbour; Alfonso Quintas-Cardama; Srdan Verstovsek; Farhad Ravandi; William Wierda; Susan O’Brien; Jorge Cortes (Haematologica, 2012)
Background Outcomes in chronic myeloid leukemia have improved with tyrosine kinase inhibitor treatment. However, little is known about outcomes of chronic myeloid leukemia in adolescent and young adult patients.Design and Methods We reviewed all 468 chronic myeloid leukemia patients treated at our institution with tyrosine kinase inhibitors as initial therapy: imatinib (n=281), nilotinib (n=98) or dasatinib (n=89).Results Median age was 47 years, median follow up 71 months and median treatment time with initial tyrosine kinase inhibitors 48 months. Adolescent and young adult was defined as aged 15–29 years. Sixty-one adolescent and young adult patients were identified. The only significant differences between adolescent and young adult and older patients were incidence of splenomegaly and distribution in Sokal risk groups. Only 3 adolescent and young adult patients have died. Rates of complete cytogenetic, major molecular and complete molecular response were significantly higher in older patients compared to adolescent and young adult patients, with a favorable trend in event-free survival for older patients. Transformation-free and overall survival were similar for the two groups.Conclusions The unfavorable trend in outcome for adolescent and young adult patients with chronic myeloid leukemia is unexpected. Additional research in this population is required to better define outcomes, understand the cause of this difference, and to help make better treatment recommendations.